Sight unseen - Swallow, James (Star Trek. Titan., 2015)
"In the wake of political upheaval across the United Federation of Planets, Admiral William Riker and the crew of the USS Titan find themselves in uncertain waters as roles aboard the ship change to reflect a new mandate and a new mission. On orders from Starfleet, Titan sets out toward the edge of Federation space to tackle its latest assignment: to work with an alien species known as the Dinac, who are taking their first steps into the galaxy as a newly warp-capable civilisation. But when disaster befalls the Dinac, the Titan crew discscovers they have unknowingly drawn the attention of a deadly, merciless enemy - a nightmare from Riker's past, lurking in the darkness."--Provided by publisher.